Flotation separation of pyrite and carbonate minerals from a carlin-type gold deposit in Guizhou by a new combined collector and its adsorption mechanism - Zhixiong Zhu; Guanghua Nie; Qiang Deng; Biyang Tuo; Tingsheng Qiu (Scientific Reports, 2024)
Abstract Flotation is the most common method for effective separation of pyrite and carbonate minerals from Carlin-type gold deposits. The effect of conventional xanthate collector on flotation of a Carlin-type gold mine in Guizhou province is poor, and it can not effectively remove carbonate minerals. In this paper, butyl xanthoxanthate and benzohydroxamic acid (BHA) were used as a new combined collector for the flotation separation of a Carlintype gold mine in Guizhou Province. The flotation behavior of pyrite and its adsorption mechanism on pyrite surface were discussed in detail through pure mineral flotation test, actual ore flotation test, contact Angle test, infrared spectrum analysis and XPS analysis. The results showed that the collection capacity of butyl xanthoxime combined with benzohydroxamic acid was obviously stronger than that of BHA or butyl xanthoxime alone. The optimal ratio of pyrite flotation with combined collector is 3, and the recovery rate of pyrite flotation is 37%, which is higher than that of pyrite flotation recovery of 30.5% when benzohydroxamic acid is used alone and 28.5% when butyl xanthate is used alone. The contact Angle test, infrared spectrum and XPS analysis showed that the combined collector of butyl xanthate and benzohydroxamic acid (BHA) produced strong chemical adsorption on the surface of pyrite. Bha can increase the adsorption capacity of butyl xanthate on the surface of pyrite, which is conducive to the flotation recovery of pyrite.